Evaluasi Dampak Demplot Macam Varietas Jagung di Kabupaten Wonogiri - Rahyunanto, Setyo (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2024)
The application of technology by farmers is one of the keys to the success of increasing crop productivity. Farmers' decisions to adopt corn cultivation technology are partly determined by the success of the demonstration plots used as examples. This study was conducted to evaluate the impact of the implementation of agricultural extension using the corn variety demonstration plot method which aims to change the attitudes and activeness of farmers in increasing corn productivity. This demonstration plot was implemented in Saradan Village, Baturetno District, Wonogiri Regency. Data collection techniques were conducted using field observation methods and interviews with farmers using questionnaire instruments. Sample determination was carried out using the simple random sampling method of 86 farmers, then analyzed using a value scale. The results of the evaluation of the impact of the corn variety demonstration plot showed that 71.03% of farmers agreed with the demonstration plot implementation process, but farmers were still in the sometimes category of 55.55% in the activeness of the production process.